IMPLEMENTASI POIN MAHASISWA - Indra Yatini; Edi Iskandar; Yoseph Yohantoro (LPPM STMIK El Rahma Yogyakarta, 2020)
Todays the needs of graduates who have hard skills or soft skills are increasing, Hardskill is obtained from academic processes such as learning during college, while soft skills are obtained from extracurricular or non-curricular activities that can form distinct and clear student characters. To encourage STMIK AKAKOM students to have good soft skills, a Student Achievement Assessment Guideline was issued as a guideline for the student and student sections in calculating the number of extracurricular and non-curricular activities of each student called the Credit Performance Unit (SKP). Each S1 student must collect 110 SKP, D3 students only need 100 SKP during the lecture period that is evenly obtained in each semester so students must start to have activities from the first semester. Every semester the SKP value must be validated by the student affairs department. Ease of validation and time efficiency is absolutely necessary, therefore a computer-based SKP management system was developed. In the system there is a database for storing SKP data, facilities for students to report their SKP, and facilities for student affairs managers